Small intestinal bacterial overgrowth is associated with intestinal inflammation in the irritable bowel syndrome - David, Liliana; Babin, Alexandru; Picos, Alina; Dumitrascu, Dan Lucian (Medicine and Pharmacy Reports, 2014)
Background and aim. Small intestinal bacterial overgrowth is encountered in bowel disorders, including irritable bowel symptoms. Low degrees of inflammation have been recently reported in the irritable bowel syndrome. We looked for the association between intestinal inflammation and small intestinal bacterial overgrowth in irritable bowel syndrome. Methods. Small intestinal bacterial overgrowth was assessed by the H2 glucose breath test in 90 consecutive patients with irritable bowel syndrome. A check-up of the oral cavity was carried out before the breath testing. Further on, the patients were classified into two groups, positive and negative, at the breath test. Then they were tested for intestinal inflammation with a fecal test for calprotectin. We used a semiquantitative test for this study. Both groups were compared for the association of intestinal inflammation with small intestinal bacterial overgrowth. Results. A number of 24/90 (26.7%) patients with irritable bowel syndrome had small intestinal bacterial overgrowth. A positive test for intestinal inflammation was significantly more frequent in patients with irritable bowel syndrome and small intestinal bacterial overgrowth (chi2: p<0.05). Conclusions. Small intestinal bacterial overgrowth is present in almost one quarter of patients with irritable bowel syndrome. It is significantly associated with intestinal inflammation.